ChemInform Abstract: Broensted Acid Catalyzed Intramolecular Hydroarylation for the Synthesis of Cycloalkenyl Selenides and Tellurides. Issue 39 (5th September 2013) - Eom, Dahan; Park, Sangjune; Park, Youngchul; Lee, Kooyeon; Hong, Gilbert; Lee, Phil Ho
Abstract The reaction of alkynyl selenides and tellurides is catalyzed by TfOH and affords the intramolecular hydroarylation products, occurring in a selective 6‐ and 7‐endo‐mode.